Application of AHP and VIKOR methods under interval type 2 fuzzy environment in maritime transportation. (1st January 2017) - Soner, Omer; Celik, Erkan; Akyuz, Emre
Abstract: The aim of this paper is to provide not only a hybrid theoretical methodology in multiple-attribute decision making problems but also a practical application in maritime transportation industry. The proposed hybrid approach integrates Analytic Hierarchy Process (AHP) method into VlseKriterijumska Optimizacijia I Kompromisno Resenje, (VIKOR) technique under interval type-2 fuzzy (IT2F) environment. While AHP and VIKOR provides a comprehensive framework to solve multiple-attribute decision making (MADM) problems in maritime transportation industry, the IT2F enables to deal with much uncertainty during linguistic assessment of decision-makers. The proposed approach is demonstrated with a hatch cover design selection problem since it has utmost importance in structure of bulk carrier ships to prevent water ingress and protect cargo form the external damages. Besides its robust theoretical insight, the paper has practical contribution to the naval engineers, classification societies and ship owners who have difficulty in deciding appropriate hatch cover type during construction of the ship. Highlights: A hybrid theoretical methodology in multiple-attribute decision making problems. A practical application in maritime transportation industry. Integration of AHP and VIKOR under IT2FSs. A practical solution for hatch cover design selection problem.